Memes, condensation symbols, and the changing landscape of political rhetoric. Issue 1 (1st January 2022) - Edwards, Jonathan J.
ABSTRACT : This article analyzes a 2019 poster of Minnesota Representative Ilhan Omar by setting it in the context of political memes. Extending recent work on meme rhetoric, and emphasizing the roll that condensation symbols and emotional appeals play in memetic display, I argue that our understanding of political messages like the Omar poster is enhanced when they are approached as memes. Such an approach considers rhetorical texts as fragments whose appeals are emotional rather than propositional and whose success lies not in winning arguments but in generating reaction and replication.